Validity and bias of academic achievement measures in the first year of elementary school. Issue 1 (2nd January 2016) - Hammes, Patricia Simone; Bigras, Marc; Crepaldi, Maria Aparecida
Abstract : We tested the criterion-related validity and potential bias of two measures of pupils' academic achievement: the Teacher Rating Scale (TRS) and the Mathematics and Literacy Achievement Tests (MLTs). These measures are representative of assessment methods largely used in the elementary school. The aims were: (1) to verify the extent to which TRS and MLTs can be predicted by external criteria collected at kindergarten and (2) to estimate the degree to which each measure might be biased by family, teacher and children's characteristics. A total of 239 children were assessed during kindergarten. At the end of the first grade, they were tested for social-emotional adjustment and academic achievement (TRS and MLTs). Results suggest that family socioeconomic status and children's school readiness at kindergarten were associated with both measures; however, the predictors accounted for significantly more variance in TRS than in MLTs. Regarding the presence of bias, results indicate that TRS seems more sensitive to children's social competence, whereas the MLTs appears to be more sensitive to pupils' anxiety.